2020
DOI: 10.1248/bpb.b19-00944
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone Protects against Pancreatic and Intestinal Injury after Acute Pancreatitis <i>via</i> Nuclear Factor-κB Signaling in Mice

Abstract: Acute pancreatitis (AP) is one kind of acute surgical abdominal disease in the world. It causes intestinal damage with subsequent bacterial migration, endotoxemia and secondary pancreatic infections. In this investigation, we determined that edaravone (EDA) reduces pancreatic and intestinal injury after AP in mice. This was demonstrated by a reduction in histological score, apoptosis, interleukin (IL)-6, IL-1β and tumor necrosis factor (TNF)-α, along with obstructing activation of Toll-like receptor 4 (TLR4) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Fan et al fabricated a nanocomposite hydrogel loaded with alginate and eudradit nanoparticles, which improved stability and solubility of contained edaravone and maximized ROS sequestration, facilitating wound healing in diabetic mice ( Fan et al, 2019 ). The alginate hydrogel promoted sustained release of edaravone, which could suppress the production of pro-inflammatory factors by inhibiting the activation of TLR4 and NF-κB ( Fan et al, 2019 ; Wang and Lin, 2020 ). Poly-lactide-co-glycolide (PLGA) has been popularlyutilized as nanoccarriers owing to its favorable biocompatibility and biodegradability.…”
Section: Empirical Sci Treatment Involving Biomaterial-based Tlr4-nf-...mentioning
confidence: 99%
“…Fan et al fabricated a nanocomposite hydrogel loaded with alginate and eudradit nanoparticles, which improved stability and solubility of contained edaravone and maximized ROS sequestration, facilitating wound healing in diabetic mice ( Fan et al, 2019 ). The alginate hydrogel promoted sustained release of edaravone, which could suppress the production of pro-inflammatory factors by inhibiting the activation of TLR4 and NF-κB ( Fan et al, 2019 ; Wang and Lin, 2020 ). Poly-lactide-co-glycolide (PLGA) has been popularlyutilized as nanoccarriers owing to its favorable biocompatibility and biodegradability.…”
Section: Empirical Sci Treatment Involving Biomaterial-based Tlr4-nf-...mentioning
confidence: 99%
“…The antioxidant properties of edaravone work by inactivating hydroxyl radical (OH) and thus, inhibiting the OH-dependent and OH-independent lipid peroxidation by supplying individual free-radicals with one of its electrons. Several reports have shown that edaravone as a potent scavenger of hydroxyl radicals has anti-apoptotic, anti-necrotic, anti-cytokine, and anti-autophagy effects in various diseases in the brain ( 11 ), heart ( 12 ), lungs ( 13 ), liver ( 14 , 15 ), testis ( 15 ), kidneys ( 16 ), pancreas ( 17 ), and small intestine ( 18 ) in animal models. Furthermore, as demonstrated in a recent study, edaravone treatment significantly relieved morphological damage and increased lipid peroxidation and apoptosis in testicular tissue by suppressing increased oxidative stress in the diabetes-induced testicular dysfunction in the rat ( 15 ).…”
Section: Introductionmentioning
confidence: 99%